A Review of Fibrocartilaginous Embolic Myelopathy and Different Types of Peracute Non-Compressive Intervertebral Disk Extrusions in Dogs and Cats - De Risio, Luisa (Frontiers in Veterinary Science, 2015)
This review discusses terminology, pathologic, clinical and magnetic resonance imaging findings, treatment, outcome and prognostic factors of fibrocartilaginous embolic myelopathy (FCEM), acute non-compressive nucleus pulposus extrusion (ANNPE) and intradural/ intramedullary intervertebral disc extrusion (IIVDE). FCEM, ANNPE, and IIVDE have a similar clinical presentation characterised by peracute onset of neurologic dysfunction that is generally non progressive after the initial 24-48 hours. Differentiating between these conditions can be challenging, however certain clinical and imaging findings can help. FCEM can occur in both adult and immature animals, whereas ANNPE or IIVDE have been reported only in animals older than 1 year. In dogs, ANNPE and IIVDE most commonly occur in the intervertebral disc spaces between T12 and L2, whereas FCEM has not such site predilection. In cats, FCEM occurs more frequently in the cervical spinal cord than in other locations. Data on cats with ANNPE and IIVDE is limited. Optimal magnetic resonance imaging (MRI) definition and experience in neuroimaging can help identify the findings that allow differentiation between FCEM, ANNPE, and IIVDE. In animals with ANNPE and IIVDE the affected intervertebral disc space is often narrowed and the focal area of intramedullary hyperintensity on T2-weighted images is located above the affected intervertebral disc